Long noncoding RNA ANRIL regulates endothelial cell activities associated with coronary artery disease by up-regulating CLIP1, EZR, and LYVE1 genes - Cho, Hyosuk (J Biol Chem, 2019)
Coronary artery disease (CAD) is the leading cause of death worldwide. Long noncoding RNAs (lncRNAs) are a class of noncoding transcripts of > 200 nucleotides and are increasingly recognized as playing functional roles in physiology and disease. ANRIL is an lncRNA gene mapped to the chromosome 9p21 genetic locus for CAD identified by the first series of genome-wide association studies (GWAS). However, ANRIL's role in CAD and the underlying molecular mechanism are unknown. Here, we show that the major ANRIL transcript in endothelial cells (ECs) is DQ485454 with a much higher expression level in ECs than in THP-1 monocytes. Of note, DQ485454 expression was down-regulated in CAD coronary arteries compared with non-CAD arteries. DQ485454 overexpression significantly reduced monocyte adhesion to ECs, transendothelial monocyte migration (TEM), and EC migration, which are critical cellular processes involved in CAD initiation, whereas siRNA-mediated ANRIL knockdown (KD) had the opposite effect. Microarray and follow-up quantitative RT-PCR analyses revealed that the ANRIL KD down-regulated expression of AHNAK2, CLIP1, CXCL11, ENC1, EZR, LYVE1, WASL, and TNFSF10 genes and up-regulated TMEM100 and TMEM106B genes. Mechanistic studies disclosed that overexpression of CLIP1, EZR, and LYVE1 reversed the effects of ANRIL KD on monocyte adhesion to ECs, TEM, and EC migration. These findings indicate that ANRIL regulates EC functions directly related to CAD, supporting the hypothesis that ANRIL is involved in CAD pathogenesis at the 9p21 genetic locus and identifying a molecular mechanism underlying lncRNA-mediated regulation of EC function and CAD development.